Polysialic acid promotes remyelination in cerebellar slice cultures by Siglec-E-dependent modulation of microglia polarization - Schröder, Lara-Jasmin; Thiesler, Hauke; Gretenkort, Lina; Möllenkamp, Thiemo Malte; Stangel, Martin; Gudi, Viktoria; Hildebrandt, Herbert (Frontiers in Cellular Neuroscience, 2023)
Multiple sclerosis is an inflammatory demyelinating disease of the central nervous system. Spontaneous restoration of myelin after demyelination occurs, but its efficiency declines during disease progression. Efficient myelin repair requires fine-tuning of inflammatory responses by brain-resident microglia and infiltrating macrophages. Accordingly, promising therapeutic strategies aim at controlling inflammation to promote remyelination. Polysialic acid (polySia) is a polymeric glycan with variable chain lengths, presented as posttranslational modification on select protein carriers. PolySia emerges as a negative regulator of inflammatory microglia and macrophage activation and has been detected on oligodendrocyte precursors and reactive astrocytes in multiple sclerosis lesions. As shown recently, polySia-modified proteins can also be released by activated microglia, and the intrinsically released protein-bound and exogenously applied free polySia were equally able to attenuate proinflammatory microglia activation via the inhibitory immune receptor Siglec-E. Here, we explore polySia as a candidate substance for promoting myelin regeneration by immunomodulation. Lysophosphatidylcholininduced demyelination of organotypic cerebellar slice cultures was used as experimental model to analyze the impact of polySia with different degrees of polymerization (DPs) on remyelination and inflammation. In lysophosphatidylcholin-treated cerebellar slice cultures, polySia-positive cells were abundant during demyelination but largely reduced during remyelination. Based on determination of DP24 as the minimal polySia chain length required for inhibition of inflammatory BV-2 microglia activation, pools with short and long polySia chains (DP8-14 and DP24-30) were generated and applied to slice cultures during remyelination. Unlike DP8-14, treatment with DP24-30 significantly improved remyelination, increased arginase-1-positive microglia ratios, and reduced the production of nitric oxide in wildtype, but not Siglec-E-deficient slice cultures. In vitro differentiation of oligodendrocytes was not affected by DP24-30. Collectively, these results suggest a beneficial effect of exogenously applied polySia DP24-30 on remyelination by Siglec-E-dependent microglia regulation.